Accelerators, Gantries, Magnets and Imaging Systems for Particle Beam Therapy: Recent Status and Prospects for Improvement - Collings, Edward W.; Lu, Lanchun; Gupta, Nilendu; Sumption, Mike D. (Frontiers in Oncology, 2022)
The paper begins by emphasizing the clinical and commercial importance of proton or other charged particle such as carbon ion therapy, refers to the manufacturers of such systems of which more than 120 are installed or under construction worldwide by April 2021. A general review of charged particle therapy systems refers to six manufacturers and provides in tabular form some details of systems installed in the US, Europe, Asia, and elsewhere. In a description of the principles of particle beam therapy a comparison is made of the properties of photons (x-rays) versus protons and protons versus carbon ions. A brief discussion of accelerators in general is followed by descriptions of cyclotrons (including the isosynchronous cyclotron and the synchrocyclotron) and synchrotrons. An interesting case study describes the evolution of a normal-conducting 220 ton cyclotron into an iron-free synchrocyclotron weighing only 5 tons. The general principles of beam handling and gantry design are described. Subsequent sections describe gantry magnets in detail - normal conducting gantry magnets, superconducting gantry magnets for proton- and carbon therapy. Mention is made of a novel CERN-designed superconducting toroidal gantry for hadron therapy, GaToroid. This device, operating under steady state current and magnetic field, is able to deliver a beam at discrete angles over a range of treatment energies. Also considered are low temperature superconducting (LTS) and high temperature superconducting (HTS) magnet windings, and the choice of REBCO conductors for cryogen-free carbon-ion gantries. Finally, the paper mentions an important “Prospect for Improvement”, viz: the introduction of MRI image guidance. A well-known property of the particle beam as it passes through tissue is its energy dependent absorption that rises to a pronounced peak (the Bragg peak) at the end of its range. In order to take advantage of this effect the exact targeting of the tumor and positioning of the patient should be guided by imaging visualization using X-ray, CT, and hopefully advanced MRI. Unlike MRI-guided photon therapy the direct interaction of the magnetic field with the charged particle beam presents a huge challenge such that MRI image-guided proton/particle therapy has not yet been available in clinical practice. Modeling studies have been undertaken on the general topic of beam-line/magnetic field interaction using, for example, the software GEANT4 (GEometry And Tracking) a platform for simulating the passage of charged particles through matter using a Monte Carlo method.